PENINGKATAN KEMAMPUAN MEMBERIKAN BANTUAN HIDUP DASAR MELALUI MODELING PARTISIPAN - Suardi Zurimi; Hamdan Hariawan; Adolfina Bumbungan (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
The drowning emergency is associated with respiratory and cardiovascular problems. Increasing public knowledge to provide first aid needs to be implemented. This study aimed to improve the ability of coastal communities to provide essential life support through participant modeling. The research design used was a quasi-experiment with a one-group pre-post test design approach. The number of samples in this study was 34 respondents. The research was conducted by determining the five models given. Then the model provides education and basic life support training to the respondents. The variables of this study were participant modeling and the ability to provide essential life support. The instrument used was the standard operating procedure for basic life support and observation sheets, and the research analysis used was the paired t-test.This study's results indicate that giving the participant modeling action has an effect and increases the average value of the respondents' knowledge and skills after being given these actions. Participant modeling can improve cognitive, self-confidence, and skills to form new behaviors, such as providing essential life support.